2018
DOI: 10.1097/md.0000000000012372
|View full text |Cite
|
Sign up to set email alerts
|

Novel biochemical predictors of unfavorable prognosis for stable coronary disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Apart from cTnI, the European Cardiology Society has endorsed both NT-proBNP and BNP to be assessed in patients with a history of ACS and in the management of heart failure 46 , 47 . Our results showed that NT-proBNP, the one with longer half-life and stability 48 , was markedly elevated in 5-FU-treated rats, demonstrating cardiomyocyte injury and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from cTnI, the European Cardiology Society has endorsed both NT-proBNP and BNP to be assessed in patients with a history of ACS and in the management of heart failure 46 , 47 . Our results showed that NT-proBNP, the one with longer half-life and stability 48 , was markedly elevated in 5-FU-treated rats, demonstrating cardiomyocyte injury and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients presenting with an acute coronary syndrome and undergoing coronary interventions, preprocedural C-reactive protein is an independent predictor of readmission to the hospital within 6 months of hospital discharge (10,22). Clearly, targeting in ammation as a way of improving outcomes in patients with cardiovascular diseases is an important initiative (14).…”
Section: Discussionmentioning
confidence: 99%
“…Although readmissions following vascular surgery are often unplanned (2,3), identi able clinical risk factors can be recognized at the time of discharge and include age, socioeconomic factors and select comorbidities (4)(5)(6)(7)(8)(9). There is emerging interest in exploring the utility of perioperative biomarkers as a means of predicting those patients who have the highest risk of adverse postoperative outcomes, including unplanned readmissions (10). Preoperative NT Pro-BNP has been recommended as an optimal means of risk-stratifying patients undergoing non-cardiac operations (11) and has been shown to have value in patients undergoing vascular surgery (12).…”
Section: Introductionmentioning
confidence: 99%
“…A number of prospective studies have consistently confirmed that a single hs-CRP measurement can independently predict vascular risk both in apparently healthy men and women that are asymptomatic for traditional risk factors of cardiovascular disease (CVD) [1,10]; and also predict risk of future coronary events in patients with acute coronary syndromes [11]. hs-CRP has been found to be the strongest predictor of coronary events compared to other novel biochemical [12] and traditional markers of CHD risks [13]. Studies have shown that there is a strong association between hs-CRP and other conditions that confers CVD risks such as metabolic syndrome, impaired glucose tolerance, type 2 diabetes mellitus and hypertension [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%